2018
DOI: 10.1007/s13311-018-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Propranolol, Bisoprolol, and Pyridostigmine for Postural Tachycardia Syndrome: a Randomized Clinical Trial

Abstract: NCT02171988.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
22
0
2
Order By: Relevance
“…Symptoms and quality of life may improve with a supervised exercise program consisting of lower-extremity supine exercises. 3 Although no drugs are currently approved by the United States Food and Drug Administration to treat POTS, fludrocortisone, 10,11 pyridostigmine, 11,12 low-dose propranolol, 13 midodrine, 14 droxidopa 15 and β-blockers including bisoprolol 10,11 may provide some benefit. Clonidine and methyldopa can be considered in neuropathic POTS.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms and quality of life may improve with a supervised exercise program consisting of lower-extremity supine exercises. 3 Although no drugs are currently approved by the United States Food and Drug Administration to treat POTS, fludrocortisone, 10,11 pyridostigmine, 11,12 low-dose propranolol, 13 midodrine, 14 droxidopa 15 and β-blockers including bisoprolol 10,11 may provide some benefit. Clonidine and methyldopa can be considered in neuropathic POTS.…”
Section: Discussionmentioning
confidence: 99%
“…37 Our systematic review identified 4 studies that evaluated beta blockers. 21,24,25,28 Metoprolol improved postural tachycardia in a study with 66 subjects and 66 controls. 21 Propranolol did not alter baroreceptor sensitivity.…”
Section: Beta Blockadementioning
confidence: 96%
“…[21][22][23][24][25][26] Two studies were randomized controlled trials. 27,28 Patients' ages ranged from 6 to 44 years, with relatively more females than males (range: 58%-95% females).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several randomized controlled trials of relatively high quality may have provided physicians with reasons to consider treating adult POTS patients with β-blockers, it is not the case with children (8, 9). Inconsistent results have been published in recent years, most of which are non-randomized, or of small sample size.…”
Section: Introductionmentioning
confidence: 99%